Fibroblast Growth Factor-Inducible-14 Is Induced in Axotomized Neurons and Promotes Neurite Outgrowth - Tanabe, Katsuhisa (J Neurosci, 2003)
For successful nerve regeneration, a coordinated shift in gene expression pattern must occur in axotomized neurons. To identify genes participating in axonal regeneration, we characterized mRNA expression profiles in dorsal root ganglia (DRG) before and after sciatic nerve transection. Dozens of genes are differentially expressed after sciatic nerve injury by microarray analysis. Induction of SOX11, FLRT3, myosin-X, and fibroblast growth factor-inducible-14 (Fn14) mRNA in axotomized DRG neurons was verified by Northern analysis and in situ hybridization. The Fn14 gene encodes a tumor necrosis-like weak inducer of apoptosis (TWEAK) receptor and is dramatically induced in DRG neurons after nerve damage, despite low expression in developing DRG neurons. Fn14 expression in PC12 cells is also upregulated by nerve growth factor treatment. Overexpression of Fn14 promotes growth cone lamelipodial formation and increases neurite outgrowth in PC12 cells. These Fn14 effects are independent of the ligand, TWEAK. Fn14 colocalizes with the Rho family GTPases, Cdc42 and Rac1. Furthermore, Fn14 physically associates with Rac1 GTPase in immunoprecipitation studies. The neurite outgrowth-promoting effect of Fn14 is enhanced by Rac1 activation and suppressed by Rac1 inactivation. These findings suggest that Fn14 contributes to nerve regeneration via a Rac1 GTPase-dependent mechanism.